Filmes finos de Zn(1-x)Cu(x)O crescidos por Spray Pirólise - Silva, Diego Scolfaro da (2017)
This work consists of investigations of the structural, morphological and optical properties of thin films of the Zn(1-x)Cu(x)O system grown on glass substrate using the Spray-Pyrolysis technique with Zinc and Copper acetates as precursors and work temperature in the range of 220°C and 300°C. Our research was based on the growth of the samples varying the Copper concentration from 0 to 100%, followed by the measurements of X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Optical Absorbance and Transmittance and Photoluminescence (PL). Finally we tested an application of the samples by studying the effects of different atmospheres on the Photoconductivity (PC). The structural characterization shows the growth of polycrystalline films with Wurtzite structure at Copper concentrations up to 10% and monoclinic structure at concentrations starting at 90%. Intermediate concentrations result in films exhibiting the two crystalline phases in coexistence. The crystalline quality accompanies this phase progression and the mean crystallite size is in the range of 9 to 14 nm. SEM images shows homogeneous surface with increasing roughness proportional to the amount of Copper. The Absorption Edge is reduced by the incorporation of Copper atoms in the structure, ranging from 3.31 eV for ZnO to 2.02eV for CuO. It is possible to detect the direct transition for all samples and an indirect for samples with copper concentration from 25%. In addition we show an increase in the absorption coefficient in the visible region. The photoluminescence of ZnO shows that the excitonic and defect-related transitions are present. The photoconductivity of ZnO is strongly dependent on point defects and the concentration of Oxygen in the atmosphere, whereas for CuO, photoconductivity shows little dependence on the atmosphere.